A cross-cultural study of acceptability and food pairing for hot sauces - Kim, Hyun-Jee; Chung, Seo-Jin; Kim, Kwang-Ok; Nielsen, Belinda; Ishii, Rie; O'Mahony, Michael (Appetite, 2018)
This study was conducted to understand the acceptance levels of hot sauces among consumers from different culinary cultures. Two newly developed hot sauces [fermented red chili pepper with soybean-paste-based sauce(GS) and fermented red chili-pepper-based sauce(KS)] were compared with Tabasco sauce(TB) and Sriracha sauce(SR). Two separate cross-cultural home-use tests(HUTs) were conducted: pizza and cream soup were provided as food items in HUT 1, whereas grilled chicken wings and rice noodle soup were provided in HUT 2. Consumers residing in Denmark, South Korea, and US participated in each HUT (n≅100 per country). Acceptance levels and the reasons for (dis)liking particular hot sauces applied to food systems were assessed. The food items that paired well with different hot sauces when the sauces were applied freely to regular meals were also analyzed among the US and Korean subjects. When the hot-sauce samples were applied to pizza and cream soup, the preferred order of the samples exhibited a cross-cultural agreement (GS = KS > TB). In the case of grilled chicken and rice noodle soup, the acceptance rating was similar for the three types of hot sauces among Koreans, whereas the acceptance was higher for SR among the US subjects for both foodstuffs, while Danish subjects preferred GS and KS over SR. The US subjects did not like hot-sauce samples with sweet and weak spiciness, whereas the Korean and Danish subjects disliked the hot-sauce sample when it was too spicy and not sufficiently sweet. These findings indicate that the matching of particular sauces with specific food items is culture-dependent, and this needs to be considered when trying to export food products such as hot sauce to other countries.